UPAYA PENINGKATAN PENGAMALAN NILAI-NILAI KEAGAMAAN MELALUI PROGRAM MADRASAH ADIWIYATA - Moch. Tohet; Alfi Wirdatus Sholehah (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
Islamic education aims to shape religious character through the practice of religious values ​​in daily life. However, the challenges of globalization and declining social and environmental awareness demand educational strategies that integrate religious values ​​with practical applications. This study aims to analyze the process of internalizing religious values ​​through the Adiwiyata Madrasah Program in improving students' religious practices at MTsN 1 Probolinggo. This study used a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation with the madrasah principal, Adiwiyata coordinator, and teachers. Data analysis was conducted using the Miles and Huberman model, which included data reduction, data presentation, and conclusion drawing. The results indicate that internalization of religious values ​​occurred through the ASIH (Clean Sunday) program, SEKAM (Waste, Energy, Biodiversity, Water, and Food), nature contemplation, and waste banks, all integrated with Islamic Religious Education learning. The program successfully improved habits of maintaining cleanliness, conserving energy and water, caring for the environment, and strengthening student discipline, responsibility, and participation in religious activities. The program's success is supported by madrasah policies, teacher exemplary behavior, and a religious school culture. While limited facilities and supervision are the main obstacles. The research findings confirm that the Adiwiyata Madrasah Program is effective as a means of internalizing religious values ​​through habituation and direct experience. The novelty of this research lies in the integrated model of environmental education and Islamic education based on Fiqh al-Bi'ah, which makes Adiwiyata not only an environmental conservation program but also an instrument for developing students' religious character.